Perceptual and Ventilatory Responses to Hypercapnia in Athletes and Sedentary Individuals - Harrison, Olivia K.; Russell, Bruce R.; Pattinson, Kyle T. S. (Frontiers in Physiology, 2022)
Purpose: Hypercapnic chemosensitivity traditionally captures the ventilatory response to elevated pressures of carbon dioxide in the blood. However, hypercapnia also contributes to subjective breathing perceptions, and previously we demonstrated a closer matching of perception to changes in ventilation in athletes compared to controls. Here we investigated any potential underlying hypercapnic chemosensitivity differences between groups, and explored whether these measures relate to ventilatory and perceptual responses during exercise as well as trait levels of affect. Methods: A hypercapnic challenge, incremental maximal exercise test and affective questionnaires were completed by 20 endurance athletes and 20 age-/sex-matched sedentary controls. The hypercapnic challenge involved elevating end-tidal PCO2 by 0.8% (6.1 mmHg) and 1.5% (11.2 mmHg) for three minutes each (randomized), with constant end-tidal oxygen. Ventilatory and perceptual responses to hypercapnia were compared between groups, and within each group the relationships between hypercapnic chemosensitivity (slope analyses) and exercising ventilation and perceptions were calculated using Spearman’s non-parametric correlations. Results: While absolute ventilation differences during hypercapnia and exercise were observed, no group differences were found across hypercapnic chemosensitivity (slope) measures. Correlation analyses revealed ventilatory hypercapnic response was related to exercising ventilation, and anxiety hypercapnic response was related to maximal exercise anxiety, but only in sedentary individuals. Conclusion: Ventilatory and perceptual hypercapnic chemosensitivity do not differ between athletes and sedentary individuals. However, ventilatory and anxiety hypercapnic chemosensitivities were related to ventilatory and anxiety responses during exercise in untrained individuals only. Athletes may employ additional strategies during exercise to reduce the influence of chemosensitivity on ventilatory and perceptual responses.